Impak kredit mikro ke atas ketaksamarataan pendapatan di kalangan sahabat Amanah Ikhtiar - Noor, Mohd Saifoul Zamzuri; Che Mat, Siti Hadijah; Abdul Hakim, Roslan (Universiti Kebangsaan Malaysia, 2013)
This paper AIMs to analyze the impact of micro credit upon the income distributions amongst the ‘Sahabat Amanah Ikhtiar’ in Kedah and Kelantan. To examine the effects on income distributions, this study used the Gini coefficient proposed by Yao (1997).The data set of this study is obtained from ‘Kajian Penyelidikan Impak 6 AIM’. A total of 495 respondents have been interviewed using the face-to-face interview method.The respondents were selected using the stratified random sampling method according to branches in both Kedah and Kelantan regions.The findings indicate that the income from activitic resources financed by the micro credit has an equalising effect upon income inequality.Assuming ceteris paribus, an increase in income share from the micro credit activitic resources will lead to a decrease in total household income inequality.